Relational Construction of Visual Objects - Skrzypulec, Błażej (Filozofia Nauki, 2015)
One of the main functions of the visual system is to construct representations of objects. These "visual objects" are formed by developing the structure of more primitive visual representations. In the article, I define the notions of "minimal visual object", "maximal-non object representation", and "constructing characteristic" that differentiates minimal objects from maximal non-objects. Based on these distinctions, I consider the type of ontological change that transforms visual regions, treated as maximal non-object representations, into basic, low-level visual objects. In order to identify such a change, I discuss theories of early vision, models of figure/ground distinction, and analytic, ontological accounts of the structure of objects. Finally, I put forward a thesis that external relations constitute the main structural factor that determines the ontological transition from non-object representations to visual objects.